Two Important Issues in Subacute Thyroiditis Management: Delayed Diagnosis and Inappropriate Use of Antibiotics. Issue 4 (18th July 2021) - Bostan, Hayri; Sencar, Muhammed Erkam; Calapkulu, Murat; Hepsen, Sema; Duger, Hakan; Ozturk Unsal, Ilknur; Ozbek, Mustafa; Cakal, Erman
Abstract : Background: Subacute thyroiditis (SAT) is a rare inflammatory disease of the thyroid gland. It has been noticed that patients with a diagnosis of SAT visit more other clinics and receive antibiotics unnecessarily. Therefore, the aim of this study was to reveal the degree of delay in the diagnosis of SAT, prediagnosis antibiotic use rates, and the awareness of clinics for the diagnosis of SAT. Methods: A total of 121 patients with SAT were enrolled in the study. A retrospective analysis was made of the history of patient symptoms during the diagnosis, which physicians they visited, antibiotic use, laboratory test results, and ultrasonographic findings. Results: The median age of the patients was 41 years. Neck pain radiating to the jaw/ear was seen in most patients (71.1%). The median time from symptom onset to a diagnosis of SAT was 23 days (range, 6–70 days). Antibiotics were erroneously prescribed to 71 patients (58.7%) before the diagnosis. The median time to diagnosis was 28 days in patients using antibiotics and 20 days in the group not using antibiotics ( p < 0.001). Two or more physicians had been visited before SAT diagnosis by 89 (73.6%) patients, and more antibiotics were prescribed to these patients than the group who visited fewer physicians ( p < 0.05). The frequency of prescribing antibiotics by physicians was 73.7% by emergency physicians, 53.1% by family doctors, 51.1% by ENT specialists, and 35.4% by internal medicine specialists. Conclusion: The diagnosis of SAT is often delayed, and misdiagnosis leads to erroneous antibiotic overuse. Physicians should increase their awareness of the diagnosis of SAT in patients with neck pain.